Empowered Resistance - Shandon C. Klein (African Journal of Gender and Religion (AJGR))
Theology plays a role in how we think about human agency for social change. One’s conception of God’s relationship to humanity, or lack thereof, can suppress or empower resistance to oppressive systems. The prophetic revolutionary fighter Aline Sitoë Diatta remains an inspirational symbol of resistance, not only for the Diola people of Senegal but also more broadly throughout West Africa. As “La femme qui était plus qu’un homme”—the woman who was more than a man—her legendary impact on subsequent generations offers the opportunity to investigate the empowering influence of the Diola indigenous faith tradition, awasena path, on moral and ethical formation. Employing the womanist theological ethics of Katie G. Cannon and Delores Williams, along with the quare theory of E. Patrick Johnson, this paper theorizes an ethic of resistance and an ethic of control. The paper will then explore Diatta’s use of both ethics based on an analysis of an African short film, À La Recherche Aline. Diatta’s embodiment of an ethic of resistance and an ethic of control within modern reenactments of her story depict her rebellion against colonialism as empowered by the awasena path and its theology. The film reflects a modern reception history of Diatta that continues to inspire those of African descent to defend against attacks on their personhood by white supremacy.